2020
DOI: 10.15586/qas2020.663
|View full text |Cite
|
Sign up to set email alerts
|

Identifying objective quality attributes of functional foods

Abstract: This study aims to identify objective quality attributes of functional foods based on literature reviews and proposing the future research agenda. There are not many articles that examined the objective quality of functional foods. This article aims to fill that gap: discussing objective quality attribute of functional foods based on the syntheses of previous studies. Previous research on objective quality of functional foods mostly came from the field of food science, and therefore applicable only to certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 126 publications
0
12
0
1
Order By: Relevance
“…In this case, a cognitive belief is represented by the belief that herbal teas carry health benefits. As a type of functional food, one of its most important objective quality attributes was health benefit (Astrini et al, 2020). In previous studies, herbal teas were said to be helpful for the maintenance of diabetes (Jayawardena et al, 2005;Zemestani et al, 2016), cholesterol level and blood pressure (McKay and Blumberg, 2006;McKay et al, 2010), and the risk level of thyroid cancer (Riza et al, 2015).…”
Section: Variables and Indicatorsmentioning
confidence: 99%
“…In this case, a cognitive belief is represented by the belief that herbal teas carry health benefits. As a type of functional food, one of its most important objective quality attributes was health benefit (Astrini et al, 2020). In previous studies, herbal teas were said to be helpful for the maintenance of diabetes (Jayawardena et al, 2005;Zemestani et al, 2016), cholesterol level and blood pressure (McKay and Blumberg, 2006;McKay et al, 2010), and the risk level of thyroid cancer (Riza et al, 2015).…”
Section: Variables and Indicatorsmentioning
confidence: 99%
“…This observation reinforced the hypothesis that consumers do not understand the product they are purchasing. This trend was confirmed by Astrini et al (2020), who point out the lack of familiarity with the term "functional" as an essential variable that affects the purchase decision, and by Carrillo, Prado-Gasc o, Fiszman, and Varela (2013), evaluating the intention to purchase functional products with 517 consumers, attesting that most participants were unaware of functional products and that people tend not to consider the importance of functional aspects in a healthy diet. However, stimuli that appeal to health, novelty/fashion, and natural content can influence the choices of this class of products.…”
Section: Processed Reduced-sodium Cheesementioning
confidence: 84%
“…These results indicate that even though it is recognized as a healthier product, the buying attitude is also related to a feeling of consumer confidence and the need for a better understanding of the product being sold. Corroborating with Astrini et al (2020), who argues that the behavior of consumers of functional foods is based on health awareness, knowledge, perception, attitude, and trust.…”
Section: Processed Reduced-sodium Cheesementioning
confidence: 99%
“…To successfully implement the blockchain technology and use it successfully, the authors sought to overcome three main challenges: motivation for the user of the smartphone application, cooperation between the parties involved and integration between the various IT systems. Astrini et al 17 identified quality objectives of functional foods based on literature reviews. Articles gathered were filtered based on their types and content.…”
Section: Case Studymentioning
confidence: 99%